2018
DOI: 10.3390/su11010122
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Productivity, Nutrients Use Efficiency, and Economics of Rice-Wheat Cropping Systems in India through Farmer’s Participatory Approach

Abstract: Rice-wheat cropping system (RWCS), a lifeline for the majority of the population in South Asia is under stress, due to the imbalanced and indiscriminate use of fertilizers. Therefore, we conducted an on-farm study at eight locations (Amritsar, Katni, Nainital, Samba, Pakur, Kanpur, Ambedkarnagar, and Dindori) covering five agro climatic zones of six Indian states (Jammu and Kashmir, Punjab, Uttarakhand, Uttar Pradesh, Madhya Pradesh, and Jharkhand) to (i) calculate the partial factor productivity (PFP) and agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…It also indicates that B and Zn interacted synergistically to boost the yield of rice crop in acid soils. Similar results were also reported by Panwar et al [24]. Kumar et al [25] also reported that application of RDF + ZnSO 4 @ 20 kg ha -1 + Borax @ 4 kg ha -1 recorded significantly higher growth and yield of rice.…”
Section: Grain Yield Straw Yield and Harvest Indexsupporting
confidence: 88%
“…It also indicates that B and Zn interacted synergistically to boost the yield of rice crop in acid soils. Similar results were also reported by Panwar et al [24]. Kumar et al [25] also reported that application of RDF + ZnSO 4 @ 20 kg ha -1 + Borax @ 4 kg ha -1 recorded significantly higher growth and yield of rice.…”
Section: Grain Yield Straw Yield and Harvest Indexsupporting
confidence: 88%
“…Increased yields of rice and wheat in the inner Terai and Terai regions of Nepal with K fertilizer application rates of 50 to 60 kg K 2 O ha -1 (Tables 2, 3, and 5) make it evident that these regions have low availability of nutrients due to sandy soil, high rainfall intensity, and frequent leaching loss of K [20]. Other findings also reported low availability of K in these regions [5,43,44]. The soils of these regions are generally characterized as fertile soil, which is made up of recent alluvial deposits, mostly fine sand and silt with light to medium texture, with the Terai region of Nepal considered the basket of grain [45,46].…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, the exchange of K is possible between available and fixed pools. More than 50% of total K availability in RWCS is obtained from fixed K pools that may further deplete the K reserve from the soil [ 44 ]. Thus, it is imperative to apply K fertilizer to maintain K levels and soil fertility in the cropland.…”
Section: Discussionmentioning
confidence: 99%
“…Balanced fertilization is one of the keys to improve fertilizer use efficiency, in principle, the concept of balanced fertilization aims at a dynamic balance between nutrient requirement and nutrient uptake by crops. Panwar et al, (2019) reported that the highest productivity of RWCS with fertilizer treatments was recorded at Amritsar, except with NPK and NPK+Zn fertilization, where Katni supersedes Amritsar. Application of N exerted a significant effect on RGEY and on an average a 106% productivity enhancement was recorded over the control across the locations.…”
Section: Balance Fertilizationmentioning
confidence: 99%